Design and comparative analysis of single-layer Graphene Microstrip patch antennas operating at Terahertz frequencies - Sahdman, Syed Abid; Islam, Kazi Shihabul; Ahmed, SK Shahabuddin; Siddiqui, Samir Sakir (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.